PEMETAAN JALUR EVAKUASI GEMPA DAN TSUNAMI DI KAWASAN PANTAI KONDANG MERAK, MALANG - Elvina Shanggrama Wijaya; Christine Wonoseputro (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The strategic geographic location of Indonesia comes with tremendous seismic and tsunami thread. This catastrophe has been recorded to be happened in a certain period of time in the past, as Indonesia is located in the meeting point of three earth’s big plateau, Indo-Australia, Eurasia, and Pacific. Java, especially in the southern part of the island, is also greatly threatened by this danger. Kondang Merak is one of the beaches in East Java, located in South Malang, that is projected to be a tourism destination, especially when the Southern Java Road has been all connected. Nevertheless, despite the hardship caused by the undeveloped condition and unfinished road, many tourists still make effort to go there and find the view worth their hardships. The lack of facility found in the site makes the presence of evacuation route mapping urgent, as the catastrophe may happen anytime. This Community Service program takes place using observation and interview methods during the Covid-19 pandemic, which mostly is done by relying on communication technology, with topographic mapping using satellite imaging, which produces three evacuation recommendation points with safe contour heights. In this research, we used digital satellite imaging to map the contour of Kondang Merak, which resulted in three evacuation node recommendations. It can focus on the details of habitable buildings, to resist and give safety to its occupant, from seismic force and tsunami in the future.